Speech by Brig. Jeneral Dato' Prof. Dr. Kamarudin Hussin UniMAP's Vice Chancellor, Chinese New Year Celebration - Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr. (Universiti Malaysia Perlis, 2010)
Event held at Dewan Kapitol, Kangar, Perlis.